NMR Dynamics Study Reveals the Za Domain of Human ADAR1 Associates with and Dissociates from Z-RNA More Slowly than Z-DNA - Lee, Ae-Ree; Hwang, Jihyun; Hur, Jeong Hwan; Ryu, Kyoung-Seok; Kim, Kyeong Kyu; Choi, Byong-Seok; Kim, Nak-Kyoon; Lee, Joon-Hwa (AMER CHEMICAL SOC, 2019)
Human RNA editing enzyme ADAR1 deaminates adenosine in pre-mRNA to yield inosine. The Z alpha domain of human ADAR1 (hZ alpha(ADAR1)) binds specifically to left-handed Z-RNA as well as Z-DNA and stabilizes the Z-conformation. To answer the question of how hZ alpha(ADAR1) can induce both the B-Z transition of DNA and the A-Z transition of RNA, we investigated the structure and dynamics of hZ alpha(ADAR1) in complex with 6-base-pair Z-DNA or Z-RNA. We performed chemical shift perturbation and relaxation dispersion experiments on hZ alpha(ADAR1) upon binding to Z-DNA as well as Z-RNA. Our study demonstrates the unique dynamics of hZ alpha(ADAR1) during the A-Z transition of RNA, in which the hZ alpha(ADAR1) protein forms a thermodynamically stable complex with Z-RNA, similar to Z-DNA, but kinetically converts RNA to the Z-form more slowly than DNA. We also discovered some distinct structural features of hZ alpha(ADAR1) in the Z-RNA binding conformation. Our results suggest that the A-Z transition of RNA facilitated by hZ alpha(ADAR1) displays unique structural and dynamic features that may be involved in targeting ADAR1 for a role in recognition of RNA substrates.
Keywords: Z-ALPHA DOMAIN; B-Z TRANSITION; NUCLEAR-MAGNETIC-RESONANCE; HUMAN EDITING ENZYME; HANDED Z-DNA; BINDING DOMAIN; ADENOSINE-DEAMINASE; PROTEIN-KINASE; CRYSTAL-STRUCTURE; COMPLEX